Adropin: a key component and potential gatekeeper of metabolic disturbances in policystic ovarian syndrome - Yildirim, B.; Celik, O.; Aydin, S. (7847050 Canada Inc, 2014)
Purpose: The aim of the current study was to evaluate potential relationships between serum adropin levels and metabolic parameters in polycystic ovary syndrome (PCOS). Materials and Methods: Twenty women with PCOS and 20 healthy, age and body mass index (BMI) matched controls were included in the study. All subjects underwent venous blood drawing on the early follicular phase after an overnight fasting. Serum adropin levels were measured with enzyme immunosorbent assay (ETA). The relationships between serum adropin levels and metabolic parameters were also assessed. Results: Serum adropin levels were found to be significantly lower in women with PCOS when compared to control group (p < 0.001). Serum adropin level was correlated negatively with fasting serum insulin levels, homeostasis model of assessment - insulin resistance (HOMA-IR) and serum lipid markers including cholesterol, very low-density lipoprotein, and triglycerides (TG) in PCOS patients (p < 0.05). Conclusion: The findings of current study suggest that women with PCOS have low serum adropin levels that may contribute to the underlying pathogenesis of metabolic disturbances in PCOS.
Keywords: Adropin; PCOS; Insulin resistance; HOMA-IR